Lithuanian peasant family as the centre of children labour upbringing (the end of the 19th – the beginning of the 20th century) - Vasiliauskas, R. (Psichologija, 1974)
For a number of centuries schooling was a privilege of the ruling classes while the greater majority of educational functions was carried out by a peasant family. The problems of labour upbringing of the peasant children are being analysed with the view of the social background of the end of 19th century and the beginning of the 20th century, while references to the general characteristics of labour upbringing of an earlier period are also made.
Keywords: peasant family; children labour upbringing